The charisma of authenticity in the Democratic Republic of the Congo - Kasper Hoffmann (Danish Institute for International Studies (DIIS), 2010)
The purpose of this paper is to propose an analysis which discloses the various interdependencies that may exist between modes of objectifying the nation and the legitimacy of discursive strategies of nation-building in the context of a grave social conflict. The paper advances two interrelated arguments. Firstly, it argues that the order of conflict in the Congo is contingent on the strictly symbolic efficacy of myths of identity. Secondly it argues that the 'charisma' of some of the country's 'Big Men' is a related to what I call the democratization of sovereignty, and neither to their supposedly exceptional individual qualities nor to a specifically African 'Big Man'-syndrome. I propose that while one must be critical of the Weberian notion of 'charisma' as a sociological theory of prophecy, one can nonetheless use the notion of 'charisma' as a tool to analyse symbolic properties that accrue to a specific individual and his followers, to the extent that they embody a subjectivity which is held as absolute by his, or their, proper discourse.
Keywords: 330